PERANCANGAN DAN IMPLEMENTASI SENSOR SUHU, KELEMBABAN UDARA, KECEPATAN ANGIN DAN CURAH HUJAN PADA PROTOTYPE SISTEM PENDETEKSI DINI KEBAKARAN HUTAN DAN LAHAN - Rio Agung Prabowo; Aris Triwiyatno; Yosua Alvin Adi Soetrisno (Transient: Jurnal Ilmiah Teknik Elektro, 2020)
Forest and land fire is a major problem happening in Indonesia. The impacts of these incidents are public health disruption, reduced forest economic value, and micro or global climate changes. Forest and land fire are not only happen in a local or national scale, but also on the international scale. This could be prevented if there is a detector designed to detect forest and land fire early. Therefore, a prototype system is designed to detect the fire in real-time so that this system could be an early warning by considering four climate and weather parameters and using 3 sensors which are DHT11 sensor to measure the temperature and humidity parameters, Anemometer sensor to measure wind speed parameters, and Raindrops Module sensor to measure the raindrops parameters. This tool is also equipped with Solar Panels as electrical power source and builds upon IoT which can detect and monitor the forest and land fire vulnerability through the website. This system is also equipped with a Fuzzy Logic-based decision-making process which provides the early warning based on the results of 4 measured parameter recitation. The output of Fuzzy Logic is a score between 0-1 that represents the “Safe”, “Danger”, and “Alert” status.